Biofilm bacteria plays a role in csom pathogenesis and has significant correlation with unsafe type csom - Artono, Artono; Purnami, Nyilo; Rahmawati, Rosydiah (Folia Medica Indonesiana, 2016)
Chronic suppurative otitis media (CSOM) may cause severe morbidity and mortality and remains a major health problem worldwide. The incidence of CSOM in Indonesia (1994-1996) is estimated at about 8.36 million people and CSOM general prevalence is 3.8% (Helmi 2005). This study aims to prove the existence of bacterial biofilm in patients with safe type and hazard type CSOM from mastoidectomy. The design was observational analytic with cross sectional approach. This study was conducted at the Teratai Wards, IBP Dr. Soetomo Hospital, and Electron Microscopy Unit, Faculty of Medicine, Airlangga University Surabaya, from November 2013 to June 2014. Samples of pathological tissues were taken by consecutive sampling and bacterial biofilms examination was done by SEM. SEM results categorized the biofilm bacteria as positive or negative. Biofilm bacteria tested positive when it shows three-dimensional representation of bacteria with clear shapes and sizes and clusters, the formation of amorphous material consisting of glycocalyx material surrounding the bacteria, and surface attachment. Biofilm bacteria was regarded as negative when there is no bacterial cluster, glycocalyx and surface attachment. This study was performed on 33 CSOM patients. Samples were divided into unsafe type CSOM (17 patients) and safe type CSOM (16 patients). Positive biofilm bacteria was found in 12 patients with unsafe type (75%) and 6 patients with safe type (35.35%). Negative biofilm bacteria was found in 4 patients with the unsafe type (25%) and 11 patients with safe type (67.9%). Logistic regression analysis revealed p value = 0.027, indicating the biofilm bacteria have a significant correlation with unsafe type CSOM (p <0.05). In conclusion, biofilm bacteria plays a role in CSOM pathogenesis of biofilm bacteria has significant correlation with unsafe type CSOM.